PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA (Studi Pada Karyawan Bagian Divisi Umum PT. PELINDO Semarang) - Andika Wijaya Kurniawan; Naili Farida; Andi Wijayanto (Universitas Diponegoro, 2013)
Human resources is one of factors has an important role in improving employee performance. The population of this study were 114 employees as respondent. From the results of data analysis conclude that Leadership Trasnformasional has significant effect on Job Satisfaction of 19.9 percent. Compensation affect Job Satisfaction by 58.8 percent. Leadership Transformasional variables affect the performance of employees by 14.8 percent. Compensation variables affect the performance of Employee by 23.7 percent. Job Satisfaction affect the employee performance by 19.3 percent. Transformational Leadership and Job Satisfaction simultaneously affecting Compensation by 60.3 percent. Transformational Leadership and Job Satisfaction simultaneously affecting Employee Performance by 27.1 percent. Transformational Leadership, and Job Satisfaction simultaneously affecting Employee Performance by 26.9 percent. Based on these results, the management of PT. Pelindo needs to consider the application of Transformational Leadership Style by division supervisor. Continuous guidance and supervision needs to be done so that employees work better. e needs of employees and the opportunity to move forward should be supported and facilitated.